Feeling the fear of many: orienting affects in Swedish austerity politics - Christine Bylund (Frontiers in Sociology)
This article investigates the emotional consequences of austerity politics targeting services and support for disabled citizens in Sweden, contributing to ongoing debates in disability studies and welfare state governance. Drawing on theories of crip phenomenology, the study focuses on how austerity policies produce affective responses—particularly fear—among disabled individuals. Based on qualitative interviews, the empirical material was collected from disabled citizens navigating the Swedish welfare system under intensified austerity measures. The research examines how these citizens experience the impact of policy reforms and the bureaucratic implementation of support reduction. The results reveal a pervasive sense of fear, disorientation, and existential insecurity, as well as increased instances of bodily harm. These affects are linked to the experience of bureaucratic violence and ableist discourse embedded in the governance of welfare services. Participants describe how these dynamics constrain their capacity to imagine and pursue viable personal futures. The article argues that austerity-driven policy changes have reshaped not only the material conditions of disabled citizens but also their emotional and social lives. It challenges the notion of ‘Swedish exceptionalism’ by illustrating how bureaucratic violence disrupts disabled individuals’ experience of full citizenship. These findings offer new insight into the relationship between affect, power, and policy in a contemporary welfare state context.